Seeking Eudaimonia-Emma in Madame Bovary by Gustave Flaubert: Feminism Existential Study - Savitri, Intan Dewi; Khotimah, Siti Khusnul; Arifin, Zulfa Rafika Ananda; Putra, Dynand Saifanza Pramesti (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2023)
This research is a Beauvoirian existential feminist study applied to the novel Madame Bovary by Gustave Flaubert. More specifically, the study on Emma focused on her goal of achieving eudaimonia or happiness. By applying the qualitative narrative method, this study focuses specifically on the characters' existence and life experiences to achieve eudaimonic conditions as they are without being weighed down in the form of normative judgments. This study contains novelty and significance because the focus on existential choices to pursue the eudaimonic conditions has not been widely applied to literary works, which will vary the situational experience and setting. As a result, the elusive eudaimonic state remains unattainable by such existential choices that do not include responsibility.